Transverse versus Vertical Incision in the Surgical Management of Placenta Accreta Spectrum - Oberlin, Austin; Yoh, Katherine; Overton, Eve; Booker, Whitney A.; Ilagan, John G.; Sassine, Dib; Diggs, Alexandra; Laifer-Narin, Sherelle; Cimic, Adela; Ring, Laurence E.; Sheikh, Maria; Clair, Caryn St.; Hou, June; Buckley De Meritens, Alexandre; Wright, Jason D.; D'Alton, Mary; Nhan Chang, Chia-Ling; Mourad, Mirella; Khoury-Collado, Fady (American Journal of Perinatology, 2024)
Traditionally, midline vertical skin incisions have been utilized during surgery for placenta accreta spectrum (PAS), as it is considered to maximize exposure and allow for a uterine incision to avoid the placenta. However, literature directly comparing outcomes of vertical versus transverse incisions in PAS is sparse. Our objective was to compare maternal outcomes between patients who underwent a vertical versus a transverse skin incision for PAS.Retrospective review of patients with pathologically confirmed PAS undergoing scheduled surgery at our institution between September 2019 and November 2023. Starting in October 2021, select patients were offered a transverse skin approach. Patients were eligible if the surgery was scheduled, and the placenta was not entirely covering the anterior uterine wall. The transverse skin incision was approximately 18 to 20 cm and used the patient's prior scar. Primary outcomes included the rate of maternal transfusion >4 units of packed red blood cells (PRBCs), the incidence of surgical complications, and the need for conversion to general anesthesia (GETA).Seventy patients underwent scheduled surgery for PAS. Thirty-three patients had a vertical skin incision, and 37 had a transverse incision. After initiation of the transverse incision approach, 37/43 (86%) had a transverse incision and none required conversion to a vertical incision intraoperatively. The two groups were similar with regard to age, body mass index (BMI; kg/m2), and severity of PAS. There was no difference in the rate of transfusion of >4 units of PRBCs (vertical 12% vs. transverse 22%, p = 0.29), or in the rate of intraoperative complications (i.e., cystotomy; vertical 3% vs. transverse 14%, p = 0.20). In patients with a transverse incision, a significantly lower number of patients required conversion to GETA intraoperatively (vertical 70% vs. transverse 24%, p < 0.001).In appropriately selected patients, a transverse skin incision was associated with lower conversion to GETA without any difference in intraoperative outcomes.
Keywords: placenta accreta spectrum; incision; anesthesia; operative; hysterectomy